The murder machine [large type] - Graham, Heather (Thorndike Press large print high octane., 2025)
"This state-of-the-art smart home has everything: a next-generation entertainment system, an ultramodern kitchen where every appliance is online, and even a personal AI to control it all. Standing above its owner's lifeless body, FBI agent Jude Mackenzie is faced with the daunting task of discovering how the woman was killed by her own home. Enter Special Agent Victoria Tennant, who reveals the stark truth: a machine can only do what it's been directed to. As the number of grisly "accidents" begins to rise, the pair must race to uncover the perpetrator even as they find themselves caught in the crosshairs! There's nowhere to hide when danger may be as close as the very phones in their pockets."--